Alteration in molecular properties during establishment and passaging of endometrial carcinoma patient-derived xenografts - Toshio Imai; Hiroshi Yoshida; Yukino Machida; Mizuki Kuramochi; Hitoshi Ichikawa; Takashi Kubo; Mami Takahashi; Tomoyasu Kato (Scientific Reports, 2023)
Abstract Patient-derived xenograft (PDX) tumor models are known to maintain the genomic and phenotypic profiles, including the histopathological structures, of the parental tumors. On the other hand, unique enrichment of single-nucleotide variants or copy number aberrations has been reported in several types of tumors. However, an understanding of endometrial carcinoma PDXs is limited. The purpose of the present study was to clarify the presence or absence of the molecular properties of endometrial carcinomas in PDXs passaged up to eight times. Established PDXs of endometrioid carcinomas maintained their histopathological characteristics, but those of carcinosarcomas predominantly consisted of sarcomatous components when compared to the parental tumors. Alterations in the proportion of cells with positive/negative immunohistochemical staining for estrogen receptor, PTEN, PAX8, and PAX2 were observed, whereas the proportions of cells with AE1/AE3, TP53, ARID1A, PMS2, and MSH6 staining were unchanged. Variants of cancer-associated genes were compared between PDXs and parental tumors. Mutations in POLE and a frameshift deletion in BRCA1 were observed in the parental tumor tissue in each of the six cases, and additional genomic alterations, which were not apparently related to histopathological and immunohistochemical alterations, were found in the PDXs of these cases. The genomic and phenotypic alterations observed between endometrial carcinoma PDXs and parental tumors were partly associated with endometrial cancer-specific characteristics related to cellular differentiation and gene mutations.